TEACHER OPINIONS ON THE COMPARISON OF MESEM AND MTAL - Özdemir, Tuncay Yavuz; Doğan, Abdulvahap; Ceylan, Esengül; Demirkol, Murat (Mustafa Hilmi ÇOLAKOĞLU, 2024)
In this research, it is aimed to determine what differences or similarities there are between MESEM and MTAL in terms of functionality, the individuals they address, and the way they operate and education. For this reason, this research was conducted based on the opinions of school administrators and teachers regarding the differences and similarities between these two institutions. This study is a qualitative research using the phenomenological design. The participants of the study were selected from a total of 26 participants, consisting of school administrators and teachers working in schools where the MESEM application was integrated in the 2023-2024 academic year in Elazığ province. According to the results of the study, it was determined that MESEM and MTAL school types provide similar qualified certification opportunities by offering students the opportunity to obtain a vocational high school diploma, mastery certificate and business opening certificate. It has been determined that the presence of MESEMs within MTAL has both positive and negative aspects. In addition, it has been revealed that especially MESEM offers students a more practical and applied education and the roles of MESEM and MTALs in vocational and technical education and to what extent they respond to sectoral needs.

Bu araştırmada MESEM ile MTAL arasında işlevsel açıdan, hitap ettiği bireyler açısından, işleyiş ve eğitim biçimi bakımından ne gibi fark veya benzerliklerin olduğunu tespit edilmesi amaçlanmıştır. Bu nedenle okul yöneticileri ve öğretmenlerin, bu iki kurum arasındaki fark ve benzerliklere ilişkin görüşlerinden hareketle bu araştırma yürütülmüştür. Bu çalışma, olgubilim deseninin kullanıldığı nitel bir araştırmadır. Çalışmanın katılımcıları Elazığ ilinde, 2023-2024 eğitim-öğretim yılında MESEM uygulamasının entegre olduğu okullarda görev yapan okul yöneticileri ve öğretmenlerden oluşan toplam 26 katılımcıdan seçilmiştir. Çalışma sonuçlarına göre MESEM ve MTAL okul türlerinin, öğrencilere meslek lisesi diploması, ustalık belgesi ve iş yeri açma belgesi alma imkânı sunarak benzer nitelikli sertifikasyon fırsatları sağladığı tespit edilmiştir. MTAL bünyesinde MESEM’lerin bulunmasının hem olumlu hem de olumsuz yönleri bulunduğu belirlenmiştir. Ayrıca özellikle MESEM'in, öğrencilere daha pratik ve uygulamalı bir eğitim sunduğu ve MESEM ve MTAL'lerin mesleki ve teknik eğitimdeki rollerini ve sektörel ihtiyaçlara ne ölçüde cevap verdiklerini ortaya koymuştur.
MESLEKİ EĞİTİM MERKEZİ ile MESLEKİ ve TEKNİK ANADOLU LİSESİ’NİN KARŞILAŞTIRILMASINA İLİŞKİN ÖĞRETMEN GÖRÜŞLERİ
Keywords: Education Management; Eğitim Yönetimi